Effect of protective coating on microleakage of conventional glass ionomer cement and resin-modified glass ionomer cement in primary molars: An In vitro study - Arthilakshmi; C Vishnurekha; Sankar Annamalai; Parisa Norouzi Baghkomeh; D Ditto Sharmin (Wolters Kluwer Medknow Publications, 2018)
Aim: The aim of this in vitro study was to evaluate and compare the effect of protective coating G-Coat Plus on microleakage of conventional glass ionomer cement (CGIC) and resin-modified glass ionomer cement (RMGIC) in primary molars. Materials and Methods: A total of 120 samples were divided into four groups with 30 samples in each group. Group A - teeth restored with CGIC. Group B - teeth restored with CGIC coated with G-Coat Plus. Group C - teeth restored with RMGIC. Group D - teeth restored with RMGIC coated with G-Coat Plus. Microleakage was tested using 2% basic fuschin dye penetration and measured at ×40 original magnification under the stereomicroscope. Results: The results of this in vitro study showed that coating with G-Coat Plus showed a reduction in microleakage in CGIC and complete absence of microleakage in RMGIC when compared to the noncoated groups, which was statistically significant. CGIC without G-Coat Plus showed highest microleakage followed by RMGIC without G-Coat Plus, followed by a relatively less microleakage in CGIC with G-Coat Plus. Conclusion: Significant reduction in microleakage was seen in conventional GIC and RMGIC with G-Coat Plus when compared to conventional GIC and RMGIC without G-Coat Plus.